Optimising the seasonal deployment of surveillance traps for detection of incipient pest invasions. (September 2019) - Kean, John M.; Stringer, Lloyd D.
Abstract: Early detection of biological invasions is necessary to enable successful management responses, such as containment and eradication. Several nations operate risk-based surveillance systems for early detection and proof of freedom from economically damaging pests and diseases. Identifying the best times of year to deploy and remove surveillance traps is important for maximising the probability of detection while minimising the economic costs of large-scale trapping. We modelled seasonal population dynamics to identify which days of the year contribute most to surveillance sensitivity and therefore the appropriate trapping period, and applied this to trapping for fruit flies (Diptera: Tephritidae) in New Zealand. Optimum trapping periods were defined as the minimum contiguous dates which would give a specific proportion (80%, 90%, 95%, or 99%) of the probability of detection compared to year-round trapping. Seasonal dynamics were based on an empirical model for the effect of temperature on population increase and decline, fitted to published data from around the world. The model suggested Mediterranean fruit fly (Medfly) should be trapped in the upper half of the North Island from at least November through May. Additional trapping in October and June may be warranted in the far north. Favourable microclimates or climate change to 2040 may allow Medfly populations to establish as far south as Christchurch and Alexandra, where trapping should run from mid December to early May. Queensland fruit fly (Qfly) and oriental fruit fly were unlikely to establish south of Napier and optimum trapping times for these species are approximately mid November through May. Climate change under moderate scenarios is unlikely to significantly alter the optimum trapping periods until at least 2040. The results were not sensitive to assumptions about trap efficacy and founder population size. However, they are based on simplified relationships between the intrinsic rate of increase and temperature. This approach is applicable to any invasive species with seasonal variation in surveillance efficacy. In response to this work, New Zealand's biosecurity authority has changed the seasonal timing of their fruit fly trapping to optimise detection efficacy. Graphical abstract: Image 1 Highlights: We modelled the optimal seasonal deployment of biosecurity surveillance traps. This approach was applied for the detection of invasive fruit flies in New Zealand. The optimal trapping season varied by location and with climate change. The results were insensitive to estimated trap efficacy or founder population size. New Zealand has changed its fruit fly trap timing to optimise detection efficacy.